Kualitas Pelayanan Di Hotel Bunda Bukittinggi Ditinjau Dari Segi Sumber Daya Manusia (SDM), Manajemen Dan Fasilitas - Rika Rika; Heliyani Heliyani (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2019)
This study aims to analyze the quality of service at the Bunda Bukittinggi hotel in terms of Human Resources, Facilities and Management. The total population in this study were all employees at the Bunda Bukittinggi Hotel, both contract employees and permanent employees, totaling 31 employees. Then the sample in this study is the entire population using the census method, which means that the entire population is sampled. Then test the research instrument with the validity test and reliability test. Before carrying out the multiple linear regression test, a classic assumption test was carried out with tests for normality, linearity, multicollinearity and so on. From the results of multiple linear regression tests, it was found that the human resource variable had a positive and significant influence on the Quality of Service at the Bunda Bukittinggi Hotel. The second variable is that management has a positive and significant influence on the Quality of Service at the Bunda Bukittinggi Hotel. The third variable, namely facilities, has a positive and significant influence on the Quality of Service at the Bunda Bukittinggi Hotel, both partially and simultaneously, which has a positive and significant influence so that all the hypotheses proposed can be accepted.